(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2025)
This article aims to compile and estimate the stock, breeding, and consumption of guinea pigs in Peru from a long-term perspective, using data from agricultural censuses and a market perspective based on household surveys, agricultural surveys, and export data. The objective is to provide a quantitative and market-oriented approach to the current situation of guinea pig breeding and consumption in Peru. The guinea pig is an important source of protein and holds significant historical and cultural value, as it was one of the first animals domesticated in pre-Hispanic times. The results reveal a lack of diversification in export markets, which are primarily concentrated in the United States. Additionally, it is revealed that companies exporting guinea pigs are often multiproduct exporters for which guinea pig is not the main product but a complementary one. Despite the significant price increases in the Peruvian agricultural sector, it is not evident that breeders directly benefit from this rise due to the high level of self-consumption. As regards sales, the main places where consumers buy guinea pigs are retail markets and street vendors. Therefore, a strategy focused on selling large quantities of guinea pigs should consider retail markets, while a strategy targeting higher prices but lower volumes could focus on exports and sales to restaurants, which have higher prices but lower sales volumes in kilograms. This study also finds that sales of guinea pigs are more regular than self-consumption. The main contribution of this article is to offer different estimates of guinea pig sales, consumption, and stock based on agricultural censuses, agricultural surveys, and household surveys, opening up the possibility for similar research on other important animal stocks. This can allow entrepreneurs, researchers, and policymakers to make more realistic projections and ground-based strategies to generate value and promote welfare. Understanding the sales and consumption patterns of these animals will help improve productivity policies and market integration for those engaged in livestock breeding.